Approximation of bounded functions by positive linear operators - Jorge Bustamante (Modern Mathematical Methods)
A general family of positive linear operators associated with a power expansion is studied. An upper estimate of the rate of convergence is obtained for bounded continuous functions in \([0,\infty)\) that has limit when \(x\to \infty\). Applications are included.